Use of criterial analysis to assess the aero-gas-dynamic perfection of surface-to-air missile - М.В. Амброжевич; А.С. Карташев; О.В. Корнєв; В.О. Середа (Системи озброєння і військова техніка)
The appearance of surface-to-air missiles (SAM) – in general and their control systems – in particular, should be determined by the experience embodied in the most advanced close analogues based on the main interrelated design conditions. These conditions should follow from the given functional purpose of the object: the method of guidance, the range and height of destruction of air targets, the characteristic type of targets, the method of launching the rocket, the construction of control system. A number of dimensionless complexes have been proposed, which, similarly to the efficiency, express the perfection of certain characteristics of missiles: transport, high-speed, high-altitude. As a necessary prerequisite for analyzing the perfection of the embodied technical solutions, a representative array of tactical and technical characteristics of missiles was used. A method for analyzing the aerogasdynamic perfection of known SAM samples and similar objects based on the theory of similarity and dimension with the use of criterion spaces is proposed. A number of examples of the application of the method for obtaining expert assessments to ensure design work at the stage of forming the appearance of missiles as part of the corresponding complexes and systems are given. An attempt was made to comprehend the relevance of the application and the prospects for further promotion of the “popular” today methods of controlling missiles (impulse micromotors), as well as the principles of “hit-to-kill”. The tendency of improving the copied missile samples and the development of the designated class of equipment is revealed.